Discrepancies between vascular and systemic inflammation in large vessel vasculitis: an important problem revisited - DİRESKENELİ, RAFİ HANER (OXFORD UNIV PRESS, 2018)
A lack of absolute correlation between systemic inflammation parameters and ongoing vascular disease activity is an important problem in some patients with large vessel vasculitis, especially Takayasu arteritis (TAK). Systemic and vascular wall inflammation in TAK are obviously interrelated, but sometimes they may act independently. There are clear discrepancies between these two types of inflammation, including cytokine patterns and responses to treatment. Vascular and systemic inflammation may also be discordant in two subgroups of giant cell arteritis. The first subgroup is mainly characterized by severe systemic inflammation mostly associated with IL-6-driven immunity, while in the second subgroup there is less systemic inflammation but prominent neuro-ophthalmic ischaemic complications characterized mostly by IFN-gamma-mediated effects. Although no definite boundaries exist, it may be suggested that the IL-6/Th17/IL-17 pathway primarily drives systemic inflammation while the IL-12/Th1/IFN-gamma pathway dominates in vascular wall inflammation both in TAK and giant cell arteritis. Immunosuppressive treatment of TAK (especially corticosteroids) initially suppresses systemic inflammation, while longer treatment duration is required for the suppression of vascular inflammation. Therefore, evaluating only the systemic inflammation may be misleading. Vascular wall inflammation is currently evaluated using expensive imaging methods, which are not feasible for repetitive use. Although pentraxin-3 is superior to erythrocyte sedimentation rate and CRP, we need more reliable biomarkers to reflect vascular wall inflammation in patients with TAK.
Keywords: Takayasu arteritis; inflammation; giant cell arteritis; GIANT-CELL ARTERITIS; REFRACTORY TAKAYASU ARTERITIS; SERUM CYTOKINE PROFILES; POPULATION-BASED COHORT; SMOOTH-MUSCLE-CELLS; DISEASE-ACTIVITY; AORTIC-WALL; ISCHEMIC COMPLICATIONS; INTIMAL HYPERPLASIA; RESTRICTED USAGE